Infectious Diseases in Internationally Adopted Children and Intercountry Discrepancies Among Screening Protocols, A Narrative Review - Elena Chiappini; Barbara Bortone; Sara Borgi; Sara Sollai; Tommaso Matucci; Luisa Galli; Maurizio de Martino (Frontiers Media S.A., 2019)
Internationally adopted children (IAC) require thorough health assessments at time of arrival in the host country. As these children are at higher risk for infectious diseases, such as gastrointestinal parasites, tuberculosis, hepatitis, syphilis, and human immunodeficiency virus, early diagnosis of infectious diseases is fundamental for the optimal management of the child and, also, to reduce the risk of transmission to the adopting community. Comparative analysis of the screening protocols adopted in Europe, the United States, and Canada revealed different approaches to the adopted children. A homogeneous and internationally shared standard of care in the management of IAC should be provided.